Analysis of Food Granary Development (Study: In Jombang Regency) - Rafisenia Herrinda Praditya; Tri Haryanto (Trunojoyo University of Madura, 2021)
The purpose of this study was to analyze the effect of government assistance, the role of members and location on the development of food storage in Jombang Regency for the period 2014-2017. This thesis studies 384 food granaries in 21 districts. The analytical method used is the Pool Least Square (PLS) by using the variable number of dependent stock grain. This study uses data from the Food Security Service of Jombang Regency, and for the use of time data from 2014 to 2017, which means that this study uses panel data. The results showed that together the government, member and location variables had a significant effect on the output of food storage development. Whereas partially the member and location variables have a positive positive effect on government assistance variables which have a significant negative effect on the output of growth stock grain in Jombang Regency.